Penerapan Akuntansi Lingkungan terhadap Kondisi Lingkungan pada Perusahaan Tambang Batu Bara - Seprenti, Dwika; Maithy, Sifera Patricia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The increase in coal mining activities in Indonesia has a significant impact on the environment. Environmental accounting is an important instrument in measuring and reporting the environmental impact of mining company activities. This article aims to analyze the application of environmental accounting in coal mining companies and its impact on environmental conditions. Using qualitative research methods based on literature studies and secondary data analysis, this study found that the application of environmental accounting is still not optimal in many mining companies. Good environmental accounting can improve transparency, accountability, and environmental sustainability.